Mechanisms and drivers of belemnite body-size dynamics across the Pliensbachian–Toarcian crisis. Issue 12 (11th December 2019) - Rita, Patrícia; Nätscher, Paulina; Duarte, Luís V.; Weis, Robert; De Baets, Kenneth
Abstract : Body-size reduction is considered an important response to current climate warming and has been observed during past biotic crises, including the Pliensbachian–Toarcian crisis, a second-order mass extinction. However, in fossil cephalopod studies, the mechanisms and their potential link with climate are rarely investigated and palaeobiological scales of organization are not usually differentiated. Here, we hypothesize that belemnites reduce their adult size across the Pliensbachian–Toarcian boundary warming event. Belemnite body-size dynamics across the Pliensbachian–Toarcian boundary in the Peniche section (Lusitanian Basin, Portugal) were analysed based on the newly collected field data. We disentangle the mechanisms and the environmental drivers of the size fluctuations observed from the individual to the assemblage scale. Despite the lack of a major taxonomic turnover, a 40% decrease in rostrum volume is observed across the Pliensbachian–Toarcian boundary, before the Toarcian Oceanic Anoxic Event where belemnites go locally extinct. The pattern is mainly driven by a reduction in adult size of the two dominant species, Pseudohastites longiformis and Passaloteuthis bisulcata. Belemnite-size distribution is best correlated with fluctuations in a palaeotemperature proxy (stable oxygen isotopes); however, potential indirect effects of volcanism and carbon cycle perturbations may also play a role. This highlights the complex interplay between environmental stressors (warming, deoxygenation, nutrient input) and biotic variables (productivity, competition, migration) associated with these hyperthermal events in driving belemnite body-size.